The Meaning Of Moral Messages In Anime Films Boruto: Naruto The Movie (Semiotic Analysis of Roland Bhartes) - Dandi Agustian; Yanto Yanto; Sapta Sari (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
Film is one of the mass communication media that very effectively conveys communication messages for humans. Boruto: Naruto the Movie is one of the films resulting from the process of visualizing comics (manga) which has become a favorite film in Indonesia. This study aims to describe the meaning of moral messages contained in the anime film Boruto: Naruto the Movie. This research is a qualitative descriptive research with Roland Barthes' Semiotic analysis approach. Data collection in this study used two techniques, namely observation and documentation. The results showed that the meaning of the moral messages contained in the anime film Boruto: Naruto the Movie includes: 1) cooperation, 2) the importance of the process in education, 3) caution in speech, 4) persistence, 5) mother's attention to her child, 6) father's attention to her child, 7) prohibition of cheating, 8) concern, 9) apologizing, 10) self-confidence, 11) mutual understanding, 12) pronouncing in, and 13) firm stance. The meaning of denotation, connotations and myths conveyed by the director and writer make Boruto: Naruto the Movie worth watching for viewers because it contains a moral message that is familiar with our daily lives.